Expanding resistances against the neoconservative project:: contributions of collectivization projects in Social Work - Mamblona, Carolina (2025)
This article proposes to discuss some current features of the rise of the new right in Argentina in the framework of a global capitalist crisis, analyzing the replacement of conservative values.  These are the pivots on which public policies and neoliberal discourses of destruction of the state focus, giving rise to the advance of the market in new areas of social life, causing a destructive destruction. Asking about the resistances seeking to characterize the challenges they contain leads us to the importance of the debate of values that counteract the common sense that the right explores on the continent, dislocating the impoverishment and degradation of life from the economic and political causes that generate it. That is why the strategic dialogue of Social Work with the collective experiences of resistance, which dispute the mercantilist and neoliberal meaning of life, is a task of first order for the profession